Correlates of child–father and child–mother attachment in the preschool years. Issue 2 (4th March 2017) - Bureau, Jean-François; Martin, Jodi; Yurkowski, Kim; Schmiedel, Sabrina; Quan, Jeffry; Moss, Ellen; Deneault, Audrey-Ann; Pallanca, Dominique
ABSTRACT: The increase in fathers' involvement in childrearing, particularly beyond infancy, warrants research exploring factors influencing the quality of child–father attachment relationships, and the impact of these relationships on children's social development. The current investigation explored various correlates of preschoolers' child–father attachment security to both parents, including contextual factors (i.e., socioeconomic status, child temperament, parenting stress), parental play sensitivity, and child social adaptation. Participants included 107 preschool-aged children (59 girls; M   = 46.67 months, SD  =  8.57) and their fathers and mothers. Results revealed that both mothers' and fathers' play sensitivity were associated with child attachment security after controlling for different contextual factors. Furthermore, the magnitude of the association between child conduct problems and child–father attachment insecurity was stronger than the corresponding association with child–mother attachment insecurity. Findings provide important information on caregiving factors associated with child–father attachment security in the preschool years and the importance of this bond to children's social adaptation.